Lipocalin-2 in Diabetic Complications of the Nervous System: Physiology, Pathology, and Beyond - Bhusal, Anup; Lee, Won-Ha; Suk, Kyoungho (Frontiers in Physiology, 2021)
Lipocalin-2 (LCN2) is a 25 kDa secreted protein that belongs to the family of lipocalins, a group of transporters of small hydrophobic molecules such as iron, fatty acids, steroids, and lipopolysaccharide in circulation. LCN2 was previously found to be involved in iron delivery, pointing toward a potential role for LCN2 in immunity. This idea was further validated when LCN2 was found to limit bacterial growth during infections in mice by sequestering iron-laden siderophores. Recently, LCN2 was also identified as a critical regulator of energy metabolism, glucose and lipid homeostasis, and insulin function. Furthermore, studies using Lcn2 knockout mice suggest an important role for LCN2 in several biobehavioral responses, including cognition, emotion, anxiety and feeding behavior. Owing to its expression and influence on multiple metabolic and neurological functions, there has emerged a great deal of interest in the study of relationships between LCN2 and neurometabolic complications. Thorough investigation has demonstrated that LCN2 is involved in several neurodegenerative diseases, while more recent studies have shown that LCN2 is also instrumental for the progression of diabetic complications like encephalopathy and peripheral neuropathy. Preliminary findings have shown that LCN2 is also a promising drug target and diagnostic marker for the treatment of neuropathic complications from diabetes. In particular, future translational research related to LCN2, such as the development of small-molecule inhibitors or neutralizing antibodies against LCN2, appears essential for exploring its potential as a therapeutic target.